High‐Performance Inverted Organic Photovoltaics with Over 1‐μm Thick Active Layers. Issue 15 (10th June 2014) - Hu, Xiaowen; Yi, Chao; Wang, Ming; Hsu, Chih‐Hao; Liu, Shengjian; Zhang, Kai; Zhong, Chengmei; Huang, Fei; Gong, Xiong; Cao, Yong
<x xml:space="preserve">Abstract</x> An efficiency of 8.62% is observed from inverted organic photovoltaics (OPVs) composed of a bulk heterojunction (BHJ) active layer with a thickness of 280 nm. Remarkably, an efficiency of 7.24% can be obtained using OPVs with a BHJ thickness of 1000 nm. Such high efficiencies from thick BHJ composite films are attributed to the high hole mobility and ordered molecular structure of the electron‐donor polymer. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>